2020
DOI: 10.1111/bjh.16405
|View full text |Cite
|
Sign up to set email alerts
|

Position paper on International Collaboration for Transfusion Medicine (ICTM) Guideline ‘Red blood cell specifications for patients with hemoglobinopathies: a systematic review and guideline’

Abstract: The International Collaboration for Transfusion Medicine Guidelines (ICTMG) has published guidance on transfusion for haemoglobinopathies. To give a UK perspective on this guidance, each of the recommendations in the ICTMG guideline were reviewed and the applicability for transfusion practice in the UK considered with reference to relevant published British Society for Haematology (BSH) guidelines and national standards . There was much consensus; however, there was disparity surrounding the recommendations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In addition, the benefit of preventive extended matching on the reduction of alloantibody formation has been extensively demonstrated in other high‐risk patients, e.g. in patients with haemoglobinopathies 13,14 and myelodysplastic syndrome 15 . Importantly, most studies did not directly compare extended with non‐extended matched patients, and reported prevalence rather than incidence 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the benefit of preventive extended matching on the reduction of alloantibody formation has been extensively demonstrated in other high‐risk patients, e.g. in patients with haemoglobinopathies 13,14 and myelodysplastic syndrome 15 . Importantly, most studies did not directly compare extended with non‐extended matched patients, and reported prevalence rather than incidence 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with SCD are at an increased risk of alloimmunisation following RBC transfusion, from both higher numbers of RBC units transfused and differences in the RBC antigens expressed (particularly RH genetic diversity) between recipient and donor populations. 1 Alloimmunisation rates are reduced by the provision of extended RH and K matched RBC units for this group of patients 2 and this is recommended by both BSH 3,4 and ASH guidelines. 5 Current BSH guidelines on RBC transfusion in SCD 3 recommend that these patients have extended RBC antigen typing performed (including C, c, E, e, K, k, Jk a , Jk b , Fy a , Fy b , S and s) at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a precision transfusion model, however, requires understanding of the red cell genotype distribution in the local haemoglobinopathy and donor populations and also the risk and specificity of alloimmunisation in different cohorts. 8 Such data are limited, and results from one country cannot readily be extrapolated to another because of the different ethnic mix of both donors and patients. 9 Several factors make this issue increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of methods for high‐throughput genotyping, including Rh variants to establish the range of major and minor blood groups for both donors and patients, this is theoretically practicable. Developing a precision transfusion model, however, requires understanding of the red cell genotype distribution in the local haemoglobinopathy and donor populations and also the risk and specificity of alloimmunisation in different cohorts 8 . Such data are limited, and results from one country cannot readily be extrapolated to another because of the different ethnic mix of both donors and patients 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation